Self-Advocacy of Students with Disabilities in Higher Education: A Bibliometric Analysis - Fitri Dwi Arini; Widiawati Widiawati (International Journal of Pedagogy and Learning Community (IJPLC), 2026)
This study examines publication trends and research developments in the field of self-advocacy among students with disabilities in higher education using bibliometric analysis. Specifically, it addresses three key questions: (RQ1) What strategies, programs, and interventions have been implemented to promote self-advocacy among students with disabilities in higher education? (RQ2) How do self-advocacy practices influence academic, social, and career outcomes for students with disabilities in higher education? (RQ3) What barriers and facilitators affect the development and practice of self-advocacy among students with disabilities in higher education? Data were retrieved from Scopus (1993–mid-2025) and screened using the PRISMA method, yielding 81 relevant records analyzed through R Studio’s Bibliometrix package.The findings show a steady growth in publications, averaging 5.16%n annually, reflecting increasing recognition of the importance of advocacy in higher education. Keyword co-occurence analysis identified four thematic clusters (1) psychological and institutional strategies for fostering advocacy, (2) curriculum and support systems, (3) outcomes such as academic persistence and career readiness, and (4) barriers including stigma and facilitation of accomodations and accessibility. Overall, the results highlight a maturing yet fragmented research domain, emphasizing the need for integrated institutional, pedagogical, and policy approaches to strengthen advocacy and equity in higher education.